TRANSLATION AS A TOOL FOR INTERCULTURAL UNDERSTANDING ON SOCIAL MEDIA: A CASE STUDY OF ENGLISH-ARABIC DIGITAL INTERACTIONS IN NIGERIA: AL-TARJAMAH BI-WAṢFIHĀ ADĀH LI-AL-TAFĀHUM BAYNA AL-THAQĀFĀT FĪ WASĀʾIL AL-TAWĀṢUL AL-IJTIMĀʿĪ: AL-TAFĀʿULĀT AL-RAQMIYYAH BAYNA AL-INJLĪZIYYAH WA-AL-ʿARABIYYAH FĪ NĪJĪRIYĀ NAMŪDHAJAN - Aliyu Okuta Ahmad (ALLAIS Journal of Arabic Language and Literature, 2026)
Translation is one of the most important indispensable means of communication between people from different linguistic backgrounds, most especially in this digital age. This study examines the role of translation as a mediating tool for intercultural understanding on social media platforms, with particular focus on English-Arabic interactions in Nigeria that is known as a multilingual and culturally diverse society, where social media has become a key space for cross-cultural communication. The research adopts a qualitative approach, which is employed to analyse the content of selected social media post, alongside case studies of intercultural exchanges. It explores how translation facilitates communication across linguistic boundaries, while also investigating instances where mistranslation or loss of cultural nuance leads to misunderstanding or conflict. The findings highlight that translation on social media functions not only as a linguistic process but also as a form of cultural mediation. While machine translation tools enhance accessibility and speed, human translation, on the other hand, proves more effective in preserving pragmatic and cultural nuances. The study contributes to the fields of Translation Studies and Digital Communication by demonstrating the complex interplay between language, culture, and technology in online environments. It also provides practical recommendations for improving intercultural communication through more culturally aware translation practices on social media platforms.